Ukrainian patronymic or language and legal illiteracy - Nelyuba, Anatoliy (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2025)
The modern life of the Ukrainian community is characterized by its transience and changeability. Some of the social innovations often indicate the incompetence of their creators and implementers, which in turn leads to negative consequences in the most diverse spheres of life; such troubles become especially noticeable in case of interference in the foundations, in age-old traditions. A visual sample-confirmation of the specified state is the state standard for the design of organizational and administrative documents, which entered into force in September 2021. The standard is noted for its orthographic and stylistic illiteracy, lack of motivation, illogicality and vagueness of some of its norms. Contrary to centuries-old traditions, this standard prohibits Ukrainians from using the patronymic name in the named documents. In this way, they were illegally deprived of the right to a name (has three components: surname, first name, patronymic) and its use in all spheres of life, provided for by the Constitution of Ukraine and other legislative acts. In addition, this standard forces Ukrainians to violate the norms of Ukrainian spelling: instead of the normative spelling of the surname with a capital letter, it obliges to write the entire word in capital letters.In fact, in the specified way, the authors of the standard laid down distorted norms of the state language in official documents, violated legislative norms, thereby setting restrictions and obstacles in the use of the state language by citizens. In the end, the innovations of this standard revealed a number of problems of the existence of the Ukrainian community, the most important of which are: the appropriateness of the level of competence and responsibility of officials, state institutions and bodies; citizen's rights, their observance and protection; preserving the identity of the Ukrainian community and its equality among other national communities. Of course, under such conditions, the specified and other features of the standard undoubtedly testify to the illegality of the mentioned provisions and the inadmissibility of its further application.